Analisis Pengaruh Inflasi, Kurs, dan Suku Bunga terhadap Indeks Harga Saham LQ45 di Indonesia - Nicho Wijaya; Wiwin Priana (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study intends to determine whether there is an effect of inflation, exchange rates and interest rates on the LQ45 stock price index in Indonesia. This type of research is quantitative, the independent variables in this study are inflation, exchange rates, interest rates on Indonesian bank certificates. The sample collection technique in this study uses annual time series data from 2010-2019. Which means the data used is 9 years. Samples that have been obtained and collected from www.investing.com, www.idx.co.id, and the Indonesian Central Bureau of Statistics, as well as through the institutions or agencies concerned in this study. The data used in this study is a type of quantitative data. The data that has been obtained will then be analyzed using multiple linear regression analysis with the Ordinary Least Square (OLS) model. The results of this study are that inflation has an effect on the LQ45 stock price index in Indonesia in 2010-2019, Exchange rates have an effect on the LQ45 stock price index in Indonesia in 2010-2019, Indonesian interest rates have no effect on the LQ45 stock price index in Indonesia in 2010 -2019, Exchange Rate Variables, Inflation, and Interest Rates simultaneously affect the LQ45 stock price index